Spacer flashover in Gas Insulated Switchgear (GIS) with humid SF6 under different electrical stresses. (March 2020) - Purnomoadi, A.P.; Rodrigo Mor, A.; Smit, J.J.
Highlights: More than 3000 humidity contents in different GIS enclosures have been collected from our case study. Humid SF6 has been found in about 20% of non-CB enclosures of Class II GIS. Humidity close to 5000 ppmV has been observed in non-CB enclosure of GIS without desiccants. By comparing the humidity content in the leaking enclosure with another sound and identical enclosure (with the same shape, current loading, and ambient conditions), there was no correlation between the humidity content and whether there is a leak on the enclosure. The latter finding leads to the interpretation that the amount of moisture passing through a leaking point is considerably neglectable. In the laboratory investigation, the test chamber is a miniature of "spacer-and-gas" model. A cylindrical epoxy resin sample (representing a spacer) is placed in between two electrodes made of stainless steel inside a small chamber and is filled with an SF6 and H2 O mixture. The gas pressure inside the test chamber represents the operating pressure in case study. Three electric field distributions have been simulated, namely, homogeneous, quasi-homogeneous, and inhomogeneous with a particle attach on the epoxy cast sample. While, the humidity content has been simulated from dry, saturation, up to condensation. It has also been observed that the flashover-drop due to condensation is higher than due to a 2-mm aluminum particle attached to the sample close to the high electric field region simulating the inhomogeneous field configuration. Abstract: Humid insulating gas (SF6 ) has been observed in a case study of 631 CB-bays of Gas Insulated Switchgear (GIS) operating under tropical conditions. The routine gas quality check in the case study reported that 20% of the non-Circuit Breaker enclosures have humidity above the value recommended by the IEEE and IEC standards. Therefore, an investigation into the flashover characteristics of a spacer in humid SF6 has been initiated in the High Voltage Laboratory of TU Delft, The Netherlands. The setup is a small model resembling the insulation system of a GIS with controlled parameters of humidity content and gas pressure. The electrical stresses in the test are AC, LI+, LI−, and SI with homogeneous, quasi-homogeneous-, and inhomogeneous field configurations. In general, the humidity does not influence the withstand strength of the spacer as long there is no condensation. When condensation occurred, the flashover voltage dropped by 28% during the test under AC at 2.6 bars, and by 38% during the test under LI+ at 2.5 bars; both with quasi-homogeneous field configuration. In the test with homogeneous field setup, the flashover voltage was dropped by 67% under LI+ at 3.4 bars. In our setup, it has also been observed that the flashover-drop due to condensation is higher than due to a 2-mm aluminum particle attached to the sample close to the high electric field region simulating the inhomogeneous field configuration.